2022
DOI: 10.46483/deuhfed.790935
|View full text |Cite
|
Sign up to set email alerts
|

Yetişkinlerin Beslenme Bilgisi ve Besin Tercihleri ile Beden Kütle İndeksi Arasındaki İlişki: Kesitsel Bir Çalışma

Abstract: Beslenme bilgisinin yeterli olması sağlıklı besin tercihleri için önemlidir. Amaç: Bu çalışmada yetişkin bireylerin beslenme bilgisi ve besin tercihleri ile Beden Kütle İndeksi arasındaki ilişkiyi belirlemek amaçlandı. Yöntem: Aralık 2019 -Mart 2020 tarihleri arasında kesitsel tasarımla yürütülen çalışmanın evrenini, İstanbul ilinin iki farklı ilçesindeki Aile Sağlığı Merkezlerine kayıtlı yetişkin bireyler oluşturdu. Örneklem, oransız tabakalı örnekleme yöntemi ile belirlendi. Aile Sağlığı Merkezlerine başvura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
0
3
Order By: Relevance
“…Öcalan et al (2020) did not find a significant difference between smoking and BMI values in their study. The results of the present study regarding BMI and smoking status was not showed similarity with the results of Keskin et al (2022)'s study. Keskin et al (2022) found a statistically significant difference between smoking and BMI.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Öcalan et al (2020) did not find a significant difference between smoking and BMI values in their study. The results of the present study regarding BMI and smoking status was not showed similarity with the results of Keskin et al (2022)'s study. Keskin et al (2022) found a statistically significant difference between smoking and BMI.…”
Section: Discussioncontrasting
confidence: 63%
“…The results of the present study regarding BMI and smoking status was not showed similarity with the results of Keskin et al (2022)'s study. Keskin et al (2022) found a statistically significant difference between smoking and BMI. In their study, 189 smokers and 255 non-smokers were included.…”
Section: Discussioncontrasting
confidence: 63%
“…In a study conducted with doctors in our country, it was determined that 53.3% of individuals had good nutritional knowledge (22). In another study conducted with adults, it was determined that 42.8% of the individuals had a good level of basic nutrition knowledge and 46.2% of them had a good level of food preference (23). The fact that the level of nutritional knowledge was higher in this study than in other studies may be due to the higher education level of the individuals.…”
Section: Discussioncontrasting
confidence: 50%